When workaholism is negatively associated with burnout: A moderated mediation - Makhdoom, Irsa Fatima; Malik, Najma Iqbal; Atta, Mohsin; Malik, Nudra; Qureshi, Madeeha Gohar; Shahid, Muhammad; Tang, Kun (Frontiers in Public Health, 2022)
Aim: The burnout is an occupational health problem that causes the devastating effects on both the employees as well as to the the organizational economy. Previous theory and research postulate that workaholism is one of the important factor that contribute to burnout. The present study aims to analyze the role of psychological capital as a mediator between the two; moreover, the study aim to examine the moderating role in the stated mediated relationship. Methods: The researchers approached a sample of university teachers (N = 1008) by using a multi-stage random sampling technique. For this purpose, DUWAS-10 (1) Oldenburg Burnout Inventory (2), Challenging Job Demands Scale (3), and Anila PsyCap Scale (4) were applied to measure workaholism, burnout, challenging job demands, and PsyCap respectively. The data obtained from the sample was subjected to analysis by using Model 14 of Process Macro by Hayes. The results confirmed the mediating role of PsyCap and moderating role of time pressure and cognitive demands in the relationship of the two variables. Results: The results confirmed the mediating role of PsyCap and moderating role of time pressure and cognitive demands in the relationship of the two variables. Conclusion: The results concluded that workaholism is not directly related to burnout rather the negative relationship exists through psychological capital and the mediated relationship is stronger for the university employees who are to face a higher level of challenging job demands including cognitive demands and time pressure.